2013
DOI: 10.2147/copd.s42366
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroid use in patients with chronic obstructive pulmonary disease and the risk of pneumonia: a retrospective claims data analysis

Abstract: BackgroundThe use of inhaled corticosteroids in patients with chronic obstructive pulmonary disease (COPD) has been associated with an increased risk of pneumonia in controlled clinical trials and case-control analyses.ObjectiveUsing claims databases as a research model of real-world diagnosis and treatment, to determine if the use and dose of inhaled corticosteroids (ICS) among patients with newly diagnosed COPD are associated with increased risk of pneumonia.Patients and methodsThis was a retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
2
6

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 43 publications
2
55
2
6
Order By: Relevance
“…Several other recent case-control studies confirm previous reports of an increased, dose-related pneumonia risk with ICS use in patients with COPD [Thornton Snider et al 2012;Yawn et al 2013;DiSantostefano et al 2014]. One study also reported a 90% relative increase in the risk of recurrent pneumonia among high-risk individuals who survived a first episode of pneumonia [Eurich et al 2013].…”
supporting
confidence: 76%
“…Several other recent case-control studies confirm previous reports of an increased, dose-related pneumonia risk with ICS use in patients with COPD [Thornton Snider et al 2012;Yawn et al 2013;DiSantostefano et al 2014]. One study also reported a 90% relative increase in the risk of recurrent pneumonia among high-risk individuals who survived a first episode of pneumonia [Eurich et al 2013].…”
supporting
confidence: 76%
“…Arguably, the most serious side effect is the increased incidence of pneumonia, which has been observed among patients with COPD both in controlled clinical trials and case-control analyses. In a recent retrospective cohort analysis on patients diagnosed with COPD [22], the use of ICS was associated with an increase in the risk of pneumonia. With regard to the risk of bone fractures associated with long-term use of ICS in the elderly population, the relative increase in fracture risk should be mostly weighted against the relative reduction of exacerbations in subjects with COPD.…”
Section: Assessment Of Risks and Benefits Associated With The Use Of mentioning
confidence: 99%
“…В по ледние годы в число нежелательных явлений тера пии иГКС у пациентов ХОБЛ также включено повы шение риска развития пневмонии. В крупном когортном исследовании [30] (n = 135 445) у больных ХОБЛ продемонстрировано статистически досто верное дозозависимое повышение риска пневмонии при использовании иГКС у больных с впервые диаг ностированной ХОБЛ: примерно на 28 % при низ ких дозах, на 111 % -при средних и на 224 % -при высоких дозах иГКС. Развитие пневмонии также сопровождается увеличением стоимости медицин ского обслуживания пациентов с ХОБЛ.…”
Section: роль игкс в терапии пациентов хоблunclassified